Respiratory Tract Viral Infections and Coinfections Identified by Anyplex™ II RV16 Detection Kit in Pediatric Patients at a Riyadh Tertiary Care Hospital. (21st November 2017) - Eifan, Saleh A.; Hanif, Atif; AlJohani, Sameera Mohammed; Atif, Muhammad
Abstract : Respiratory infections are caused by an array of viruses, and limited information is available about viral coexistence, comparative symptoms, and the burden of illness. This retrospective cohort study aimed to determine the etiological agents responsible for respiratory tract infections by Anyplex II RV16 detection kit (RV16, Seegene), involving 2266 pediatric patients with respiratory infections admitted to the Department of Pediatrics at King Abdul-Aziz Medical City, Ministry of National Guard, Riyadh, from July 2014 to June 2015. The most frequent respiratory infections were recorded in the 1 to 5 year age group (44.7%). Rhinovirus (32.5%), Adenovirus (16.9%), and Respiratory syncytial virus (RSV) B (10.4%) were most common. In single viral infections, Rhinovirus (41.2%), Metapneumovirus (15.3%), and Bocavirus (13.7%) were most frequent. In multiple viral infections, Rhinovirus (36.7%), Adenovirus (35.2%), Bocavirus (11.2), RSV B (7.8%), and RSV A (6.7%) were most frequent. No significant difference was observed in clinical presentations; however, rhinorrhea and hypodynamia were significantly associated with viral respiratory infections. Most respiratory viral pathogens peaked during December, January, March, and April. Rhinovirus, Adenovirus, and Bocavirus circulations were detected throughout the year. Winter peaks were recorded for Rhinovirus, RSV B, Adenovirus, and RSV A, whereas the Metapneumovirus, and the Bocavirus peaked in March and April. These findings enhance understanding of viral etiology and distribution to improve respiratory infection management and treatment.